Stories of struggles and success: Unveiling the societal pressures among professional unmarried women - Quimosing-Ocay, Abigail; Mamaril, Daisy A; Taclawan, Jay France D.; Bulwayan, Ronald B. (Edelweiss Applied Science and Technology, 2025)
Despite growing societal interest in the experiences of professional unmarried women, research often overlooks their specific vulnerabilities and challenges, particularly within the Philippine context, specifically in Kalinga province. This phenomenological study explored the lived experiences of professional unmarried women regarding their concept of success, the struggles they face in their personal and professional lives, the impact of these struggles on their mental health and social well-being, and their coping strategies. The research disclosed that success is viewed by these women through the themes of career and position, health, and peace of mind. Their struggles often stem from societal pressures, emotional needs, cultural issues related to marriage and career, health issues, bullying, and discrimination in the workplace. These experiences were found to have implications for their mental health, potentially leading to anxiety and depression, and their social well-being, including stigma and social isolation, feelings of inadequacy through social comparison, and confusion between societal norms and personal values. Despite these challenges, the women employed coping strategies such as diverting attention to family and loved ones, keeping themselves busy, practicing self-acceptance and self-care, and engaging in church activities while maintaining faith. The study is grounded in social role theory and intersectionality theory, highlighting the influence of societal expectations and the intersecting nature of gender, marital status, and profession on the experiences of these women. The findings provide a deeper understanding of the complexities faced by professional unmarried women in navigating societal norms while pursuing professional success.